Mary Pope Osborne's Magic Tree House : Pirates Past Noon - Book 4 4, Pirates past noon - Laird, Jenny, 1969-; Matthews, Kelly (Comic book artist); Matthews, Nichole; Osborne, Mary Pope. (New York : Random House Children's Books, 2022)
"The magic tree house whisks Jack and Annie to an island in the Caribbean where they dig up buried treasure with real-life pirates"--
Keywords: Pirates -- Comic books, strips, etc; Time travel -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Tree houses -- Comic books, strips, etc; Pirates -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Cartoons and comics; Time-travel comics; Graphic novels